Saúde reprodutiva e transtornos mentais comuns em mulheres de Feira de Santana - Bahia - Barbosa, Hayana Leal (2007)
Women have lived over the years and the reproductive function in private domestic service. However with their increasing entry into the labor market may cause the appearance of mental illness. Common Mental Disorders (CMD) have gained prominence, especially in women beyond the risk factors referred to gender, are still exposed to factors inherent in pregnancy, childbirth and postpartum. Emotional components associated with the life-cycle factors such as age, marital status, number of children, female headed households, recreation, informal working double shifts and work of family care may intensify the psychological distress among the female population. In order to evaluate the association between the characteristics of Reproductive Health and the MDP, we performed a cross-sectional study, including women living in urban areas of Feira de Santana aged over 15 years. The TMCs were assessed by the Self Reporting Questionnaire (SRQ-20). Were calculated prevalence ratios and univariate analysis was performed and stratified. The overall prevalence of CMD was 39.5%. Higher prevalence of mental disorders were observed in women over 50 years, with low education, black, widowed or separated, with the onset of sexual activity before age 19, with children, who did not use contraceptive methods and were in the climacteric. Was performed stratified analysis of the association between age at first sex, presence of children, abortion and menopause to TMC and sociodemographic covariates, occupational and recreational activities. It is inferred that health policies should increase their activities providing assistance to sexual and mental health of women, providing care to fully considering their individuality and rights without discrimination of race and class in the municipality of Feira de Santana-Ba.